Inclusive Leadership Promotes Challenge-Oriented Organizational Citizenship Behavior Through the Mediation of Work Engagement and Moderation of Organizational Innovative Atmosphere - Chen, Lu; Luo, Fan; Zhu, Xiaomei; Huang, Xinjian; Liu, Yanhong (Frontiers in Psychology, 2020)
Challenge-oriented organizational citizenship behavior—or the organization-improving tasks employees perform beyond their job description—is important for high organizational performance, but the organizational factors influencing it are poorly understood. In this study, we explored how inclusive leadership influences employees’ challenge-oriented organizational citizenship behavior in the Chinese context, drawing on data from 558 employees in high-tech industries. Multivariate correlation analysis showed that inclusive leadership promotes employees’ challenge-oriented organizational citizenship behavior, and that this influence is partly mediated by work engagement. Further, it showed that organizational innovative atmosphere has a moderating effect on the relationship between inclusive leadership and employees’ challenge-oriented organizational citizenship behavior. In effect, this study expands the range of predictive variables for challenge-oriented organizational citizenship behavior and provides not only theoretical insight but also practical guidance for leaders who seek to motivate this behavior in their employees.